The spurious dragonfly: the intricate nomenclatural problems regarding the names Libelloides and libelluloides (Neuroptera Ascalaphidae et Myrmeleontidae) - Pantaleoni, Roberto A.; Loru, Laura (Zootaxa, 2018)
Around 1970 Tjeder suggested two changes to the nomenclature of the Ascalaphidae regarding the names Libelloides and libelluloides. To avoid future confusion, we augment Tjeder’s work by analyzing the nomenclatural status of all taxa related to these names—specifically Libelloides Schäffer, 1763 and Libelloides coccajus ([Denis et Schiffermüller], 1775), Ascalaphidae, and Palpares libelluloides (Linnaeus, 1764), Myrmeleontidae. After a short historical preamble, we treat the three taxa in chronological order of description. Additional information is reported in four Addenda, followed by a list of synonymies. Our conclusions are as follows: 1. Schäffer’s Das Zwiefalter– oder Afterjüngferchen (1763) is consistent with the Principle of Binomial Nomenclature, thus the names Libelloides and Libellula spuria, therein created, are available [ICZN Code Article 11.4.1.]. 2. Libellula spuria Schäffer, 1763, is a senior synonym of Papilio coccajus [Denis et Schiffermüller], 1775; however, the older name Libellula spuria Schäffer, 1763, is a nomen oblitum with respect to the younger name Papilio coccajus [Denis et Schiffermüller], 1775, which therefore must be considered a nomen protectum [ICNZ Code Article 23.9.2: both Articles 23.9.2.1 and 23.9.2.2 apply]. 3. The name Hemerobius libelloides Linnaeus, 1764, is the correct original spelling [ICNZ Code Article 32.5.1 does not apply], but the subsequent spelling Myrmeleon libelluloides Linnaeus, 1767, even if an unjustified emendation [ICZN Code Article 33.2.1 and 33.2.3], is in prevailing usage and consequently: i) it is deemed to be a justified emendation, and ii) it is attributed to its original author and date [ICZN Code Article 33.2.3.1]. 4. Myrmeleon libelluloides Fuesslin, 1775, being a mere misidentification of the name Myrmeleon libelluloides (Linnaeus, 1764), is unavailable name [ICZN Code Article 49]. 5. Schäffer (1763) is not the author of the name Ascalaphus libelluloides: the authorship must be attributed to van der Weele with the date of description 5th January 1909. 6. Libellula turcica Petiver & Empson, 1767, in Ábrahám (2012), is an unavailable name. 7. The original spelling Myrmeleon kolywanense Laxmann, 1770, is the correct original spelling [ICNZ Code Article 32.5.1 does not apply], but the subsequent spelling Ascalaphus kolyvanensis Rambur, 1842, even if an unjustified emendation [ICZN Code Article 33.2.1 and 33.2.3], is in prevailing usage and consequently: i) it is deemed to be a justified emendation, and ii) it is attributed to its original author and date [ICZN Code Article 33.2.3.1]. 8. Fuesslin’s Verzeichniss der ihm bekannten schweizerischen Insekten (1775) was published between 24th February (date in the second part of the Preface [Vorrede]) and 12th May 1775 (Wyttenbach, 1775), so the date of publication is 12th May 1775 [ICZN Code Article 21.3].